PENURUNAN KANDUNGAN PHOSPHAT PADA LIMBAH CAIR INDUSTRI PENCUCIAN PAKAIAN (LAUNDRY) MENGGUNAKAN KARBON AKTIF DARI SAMPAH PLASTIK DENGAN METODE BATCH DAN KONTINYU (Studi Kasus : Limbah Cair Industri Laundry Lumintu Tembalang, Semarang) - Wisnu Wardhana, Irawan; Siwi Handayani, Dwi; Ika Rahmawati, Dessy (Diponegoro University, 2009)
Increasing the number of laundry industry influences on the increasing of detergent utilizzation. Thedominant substance contained in the detergent is Natrium Tripolyphosphat, a builder and surfactant.Therefore the waste contains Phosphate. Most of the laundry industry throw their waste without treatmentfirst. The waste would cause Eutrofication where the water body became rich of dissolved nutrient,descending of the dissolved oxygen and capability of water body assist power to water biota. Lumintu isone of the laundry industries which located in Tembalang district. According to the result of preexperiment,industrial waste water containes 10,21 mg/l phosphate. This value exceeds standard quality ofPerda Prov. Jateng no. 10 year 2004 about maximum value for total of phosphate is 2 mg/l. One ofwastewater treatment method is adsorption using the active carbon from plastic rubbish kind ofPolyethylene. This reseach purposes to know the capability of active carbon from plastic rubbish inreducing phosphate content with batch and column operation. The batch operation use 1,2 and 3 gramvariation weight active carbon from plastic rubbish for 30 - 60 mesh and 100 - 200 mesh variation mediasize. The batch operation has 45,45 % from the highest phosphate efficiency lowering on the 3 gram.Otherwise, column operation need 1 inch column diameter with 50 ml/minute and 100 ml/minute debitvariation. Continue trial had 54,75 % from the highest phosphate efficiency lowering on the 50 ml/minute.Constant value speed (k1) is 0,0108 ml/mg.s with capacity of adsorption (qo) 0,677 mg/g.